2020
DOI: 10.3389/fmars.2019.00797
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Benthic Microbial Community Underlying the Phaeocystis antarctica-Dominated Amundsen Sea Polynya, Antarctica: A Proxy for Assessing the Impact of Global Changes

Abstract: Polynyas in the polar seas are regarded as windows through which ecosystem responses associated with global climate changes are to be noticed. However, little information is available on benthic microbial communities in the Amundsen Sea polynya (ASP), where environmental changes due to global warming are occurring rapidly, from which future climate change-induced ecosystem responses could be assessed. We performed high-throughput sequencing of 16S rRNA genes and quantitative PCR in combination with biogeochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 98 publications
(133 reference statements)
2
8
0
Order By: Relevance
“…As with the water column, Proteobacteria were the dominant bacterial phylum in the sediments (∼25% on average across all samples) and occurred in all samples except KC06 170 cmbsf. This result is consistent with previous studies on Southern Ocean and Antarctic sediments, which found Proteobacteria to be relatively abundant in sediments (Cho et al., 2020; Learman et al., 2016). Therefore, Proteobacteria seem to be able to survive in both ocean and sediment environments, with the DNA detected in the sediment record possibly being a mix of modern and ancient Proteobacteria DNA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As with the water column, Proteobacteria were the dominant bacterial phylum in the sediments (∼25% on average across all samples) and occurred in all samples except KC06 170 cmbsf. This result is consistent with previous studies on Southern Ocean and Antarctic sediments, which found Proteobacteria to be relatively abundant in sediments (Cho et al., 2020; Learman et al., 2016). Therefore, Proteobacteria seem to be able to survive in both ocean and sediment environments, with the DNA detected in the sediment record possibly being a mix of modern and ancient Proteobacteria DNA.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, Proteobacteria seem to be able to survive in both ocean and sediment environments, with the DNA detected in the sediment record possibly being a mix of modern and ancient Proteobacteria DNA. Proteobacteria are often found in diatom‐dominated waters (Cho et al., 2020; Learman et al., 2016), which may be useful for sed aDNA studies in which diatom sed aDNA is difficult to extract, as the Proteobacteria signals may be indirectly reflecting past diatom presence. However, more research is required to confirm whether the apparent co‐occurrence of proteobacteria (or specific proteobacteria orders) could be used as a proxy of primary producers’ presence in surface waters and whether these eukaryote–bacteria associations could be explored as paleo‐composition indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, much less is known about the effects on benthic microbial communities, the key drivers of organic matter remineralization processes and biogeochemical cycling (Falkowski et al, 2008). Previous polar studies have shown that the quality and quantity of organic matter are major drivers of microbial diversity and community composition, with certain taxonomic groups showing strong affiliations with environmental parameters such as sediment algal pigment concentration and total organic carbon (TOC; Bienhold et al, 2012;Ruff et al, 2014;Learman et al, 2016;Cho et al, 2020). However, few studies in Antarctica have characterized the benthic microbial communities, and none have compared the effects of FYI and MYI, which may provide a unique perspective on marine ecosystem functioning in these difficult to study and rapidly changing polar environments.…”
Section: Introductionmentioning
confidence: 99%
“…Marine sediment is an important repository of organic matter and nutrients that are deposited mainly from seawater and land ( 3 ). In particular, the microorganisms in sediment play an important role in the biogeochemical cycle of the ecosystem, including the decomposition of organic matter and the circulation of nutrients ( 4 , 5 ). Nevertheless, monitoring of the marine pollution in Geoje-Hansan Bay is mainly focused on water quality management ( 6 ), and the sediment is managed mainly using organic matter ( 1 ).…”
Section: Announcementmentioning
confidence: 99%